Differentiated/undifferentiated mixed type is a prognostic factor for T2/T3 gastric cancer patients. (2nd November 2021) - Lu, Huiwen; Sun, Yimeng; Zhu, Zirui; Xu, Huimian; Huang, Rui; Huang, Baojun
ABSTRACT: Objectives: This work aimed to find the association of mixed-type histology and prognosis of T2/T3 GC patients. Methods: Eligible T2/T3 gastric cancer patients at our institution were identified. The histological types and risk factors affecting OS were examined. Survival differences were assessed by log-rank tests and Kaplan–Meier curves. Results: The study identified 972 T2/T3 gastric cancer patients, including 283 differentiated-type patients, 544 undifferentiated-type patients and 145 mixed type. Mixed-type histology was associated with shorter 5-year OS (DT vs UDT vs MT:57.5% vs 44.9% vs 39.6%, P = 0.002). MT histology can be predictive for prognosis of T2/T3 GC patients (HR for OS: 1.386, 95% CI: 1.028–1.868, P = 0.032), and its malignant potential is not inferior to UDT. In the subgroup analysis, MT can potentially be independent risk factor for non-distal GC patients ( P = 0.010). Conclusion: This study reported that mixed histology could be regarded as a potential prognostic factor for T2/T3 gastric cancer patients, especially for those with non-distal cancer. MT patients have higher incidence of metastasis and recurrence and had poorer prognosis than those with pure histological type. It is necessary for MT patients to have preoperative pathological examination for accurate histologic classification, so as to make the comprehensive treatment strategies..